PENGGUNAAN RAGAM BAHASA INDONESIA DALAM KOMUNIKASI MAHASISWA DI ERA DIGITAL - Siti Nurhaiza; Erhanif Fadillah; Rivan Mansurin; Sutan Salsabila; Raina Anatu Qalbi; Kasih (Journal of Research and Publication Innovation, 2025)
Indonesian language has various forms depending on its context and usage situation. In the current digital era, university students as active social media users exhibit dynamic variations in language use. This study aims to describe the types of Indonesian language variations used by students and to identify factors influencing their language choices. This research employs a descriptive qualitative method with observation and interview techniques involving students at Universitas Pamulang. The results indicate that students tend to use informal language variations in online communication, while formal language remains used in academic contexts. This shift reflects the influence of digital media on linguistic behavior, yet it does not entirely replace the use of proper Indonesian.